Upaya Guru BK untuk Mengentaskan Masalah-Masalah Perkembangan Remaja dengan Pendekatan Konseling Analisis Transaksional - Netrawati, Netrawati; Khairani, Khairani; Karneli, Yeni (ISLAMIC COUNSELING: Jurnal Bimbingan Konseling Islam, 2018)
Adolesent faces complicated phase because the condition of unstable emotion. In beginning of adolesecence, the development shows strong sensitive and reactive characterisic to an event or social situation. The emotion is negative and temperamental. This research has purpose to: 1) helping student to solve developmentâs problems by using approach of transactional analysis counseling, 2) giving skill for counseling guidance teacher to be able to use approach on transactional analysis counseling by using life position technique, 3) helping adolecent to reach life position in gaining optimal development. This research uses descriptive method through the study of action research which consist of two cycles. The first cycle with counseling plan by using approach of transactional analysis counseling, and second cycle by giving perception and action whith approach of transactional analysis counseling. The subject of this research is student of junior high school as well as counseling guidance teacher. Instrument and technic of data accumulation is interview and observation. The result of it will increase the skill of counseling guidance teacher in doing conseling intervention and group of transactional analysis focuses in solving adolescentâs problem. Overall of those two cycles have the change of skill that counseling guidance teacher has to help solving adolescentâs development especially showing correct ego state and life script is I am ok you are ok.